Continuance intention of e-learning: The condition and its connection with open innovation - Amalia Suzianti; Sabrina Ayu Paramadini (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Recently having increased every year, in 2017, e-learning's worldwide average growth rate was 7.9% with a worldwide market of USD 52.5 billion. Holding all nations' eighth highest e-learning growth rate, Indonesia had a market of USD 12.2 billion, with a growth rate of 25% in 2017. Obviously, Indonesia has great potential to develop a greater, even more prospective e-learning business. In fact, the Republic of Indonesia's Minister of Education and Culture plans to make e-learning permanent by changing traditional into hybrid learning, including at the primary school level. Consequently, this study recommended strategies for increasing "continuance intention" for e-learning in primary schools. A conceptual model was developed based on the Expectation-Confirmation Model of Information System Continuance and the Information System Success Model. The study's model development involved 195 teacher-respondents and used the partial least squares structural equation modeling for data analysis. Four of 11 hypotheses were rejected because they did not meet the requirements, but based on other results, 10 strategic recommendations were submitted to and assessed by several experts who used the integrated method of Importance-Performance Analysis and Kano to select four strategies selected as improvement priorities and three as keep-up-the-good-work priorities.
Keywords: 650; information system success model; e-learning; expectation-confirmation model of information system continuance; importance-performance analysis; kano model; PLS-SEM; primary education